1998
DOI: 10.1111/j.1151-2916.1998.tb02501.x
|View full text |Cite
|
Sign up to set email alerts
|

Dense Perovskite, La1‐xA′xFe1‐yCoyO3‐δ (A′= Ba, Sr, Ca), Membrane Synthesis, Applications, and Characterization

Abstract: La 1−x A x Fe 0.8 Co 0.2 O 3−␦ (A = Ca, Sr, Ba) perovskite powders were synthesized to attain the desired properties of high O 2 flux and stability under reducing conditions. Steady-state oxygen permeation rates for La 1−x A x Fe 0.8 -Co 0.2 O 3−␦ perovskite membranes in nonreacting experiments with air on one side and helium on the other side of the membrane were in the order A x = Ba 0.8 > Ba 0.6 > Ca 0.6 > Sr 0.6 . Partial oxidation of methane to syngas (CO + H 2 ) was performed in a dense La 0.2 Ba 0.8 Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(55 citation statements)
references
References 15 publications
2
53
0
Order By: Relevance
“…Perovskite-type MIEC membranes without Ba 2+ and Sr 2+ doped in the A-site usually show low oxygen permeation flux. For example, the oxygen permeation flux of LaCoO 3 perovskite was less than 0.03 mL cm À2 min À1 for a 0.41 mm thick membrane at 1000°C [25], and the oxygen permeation fluxes of LaGa 1ÀxÀy Co xMg y O 3Àd membranes were no larger than 0.05 mL cm À2 min À1 for the 1.0 mm thick membranes at 950°C, while the permeation fluxes of the Ba 2+ and Sr 2+ doped LaCoO 3Àd perovskite-type MIEC membranes were usually more than ten times higher than that of the parent membranes [26,27]. Therefore, the doping of alkaline earth metal ions in the perovskite A-site is important for MIEC [28], and found that the membranes were stable for oxygen permeation when CO 2 was used as the sweeping gas at temperature 850°C.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite-type MIEC membranes without Ba 2+ and Sr 2+ doped in the A-site usually show low oxygen permeation flux. For example, the oxygen permeation flux of LaCoO 3 perovskite was less than 0.03 mL cm À2 min À1 for a 0.41 mm thick membrane at 1000°C [25], and the oxygen permeation fluxes of LaGa 1ÀxÀy Co xMg y O 3Àd membranes were no larger than 0.05 mL cm À2 min À1 for the 1.0 mm thick membranes at 950°C, while the permeation fluxes of the Ba 2+ and Sr 2+ doped LaCoO 3Àd perovskite-type MIEC membranes were usually more than ten times higher than that of the parent membranes [26,27]. Therefore, the doping of alkaline earth metal ions in the perovskite A-site is important for MIEC [28], and found that the membranes were stable for oxygen permeation when CO 2 was used as the sweeping gas at temperature 850°C.…”
Section: Introductionmentioning
confidence: 99%
“…However, to realize the process, the membrane is required possessing both high permeation flux and stability under syngas atmosphere. Among the developed materials, cobalt-doped Ln x (Ba,Sr,Ca) 1−x Co y Fe 1−y O 3−ı (Ln: rare earth metal, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1) usually have high oxygen permeation fluxes but are unstable under reducing environments and long-term operation at high temperatures [11][12][13][14][15][16][17][18][19][20]. Ln x (Ba,Sr,Ca) 1−x Fe y (Zn,Al,Ga,Ti,Zr,Ce) 1−y O 3−ı (0 ≤ x ≤ 1, 0 ≤ y ≤ 1) usually possesses high stability under reducing environments but poor permeation fluxes [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…2 These patterns confirm that the rich carbon porogenic agent has not affected the crystal structure in the sintered porous substrate. This is an important point as the combustion of activated carbon embedded in the perovskite matrix during calcination in air at high temperatures generated CO 2 , which has the propensity to form carbonates [43][44][45], thus affecting the BSCF structure. This is not the case in this work as no secondary phases containing metal oxides were observed in the XRD patterns.…”
Section: Resultsmentioning
confidence: 99%